Non-invasive physiological wearable sensor real time monitoring - Alharbi, Samah (2015)
This project presents the implementation of reflectance Photoplethysmography (PPG) and thermo-chip sensor-¬based wireless architecture for a human health monitoring system. The thermo-¬‐chip sensor is used to continuously monitor the body temperature, while the reflectance PPG sensor is used to measure the heart rate by an optical technique that senses the blood volume change in the tissues and vessels. The sensors outputs are then given to the signal conditioning circuit used to filter the noises and amplify the signals. These signals are interfaced with a PIC microcontroller and data is transmitted to the node wirelessly using a Bluetooth module, which passes the data to a PC using a serial communication port. The readings measurement data are continuously monitor as a real time display on the graphic user interface (GUI). The proposed PPG sensor is used to overcome the limitations of current sensors such as restriction of measurement site and movement. The red and IR source lights are commonly used with current sensors and both light sources are easily corrupted with movement. However, in this study, the designed PPG sensor includes a green source light that uses as a robust wavelength against movement since the short wavelength penetrates near to the surface where small vessels present; thus, small vessels have less influence and minimal effect contamination on the PPG signal. In addition, the PPG sensor is designed to be in reflectance mode, which was found to help to apply and attach the reflectance sensor on different positions on the body such as finger, palm forehead and arm. With these approaches, users would be more comfortable and move more, without any restriction unlike the current transmission sensors which are commonly used on the finger. Furthermore, in this study, wireless monitoring is used without any restriction of nearby cable. The data obtained from the designed sensor were compared and analysed against commercial devices. The results show high agreement and no significant differences between data. The results and observations of this study demonstrate the goal of a high performance, wearable sensor that could be feasible and viable.